Методологічні основи дослідження проблеми інклюзивної освіти дітей дошкільного віку - Кузава, Ірина Борисівна; Kuzava, Iryna B. (Сумський державний педагогічний університет імені А. С. Макаренка, 2015)
У статті схарактеризовано сучасний етап розвитку у практиці навчання і виховання результатів наукових досліджень, пов’язаних з упровадженням інклюзивної освіти дітей дошкільного віку. Обґрунтовано методологічні основи досліджуваної проблеми. Проаналізовано сутність понять „методологія”, „інклюзія”, „інтеграція”. Окреслено провідні параметри педагогічної сутності інклюзивної освіти дошкільників. Визначено основні відмінності інклюзивної освіти від інтегрованої освіти. The article described the current stage of development in the practice of training and education research results related to the introduction of inclusive education of preschool children. Grounded methodological basis of the problem of inclusive education of preschool children requiring correction of mental and physical development. The essence of the concepts of "methodology", "inclusion", "integration". Outlined leading educational settings essence inclusive education of preschool children. The main difference from an integrated education Inclusive education: educational environment adapting to the individual characteristics of the child; access to education for all pupils; mutual support, mutual support and common vzayemonavchannya in the process of not only children but also adults; special activities on the organization of joint teacher of preschool children with different levels of mental and physical development. It is alleged that an inclusive approach - a strategy that is based on the basic theoretical positions of inclusive education, which provides joint training and education of people with different levels of mental and physical disorders on the basis of equality and tolerance towards each other. Found that the core values of inclusive education are: the right of everyone to education; enrollment of children with different levels of mental and physical development; help in learning each pupil; learning difficulties in certain areas or at certain times; the main responsibility of educational institutions, teachers, children and parents for cooperation in education; the constant support of teachers. It is proved that the methodology of inclusive education should focus on transfer theories, rules, training of persons with mental and physical disorders to their healthy peers.
Methodological bases of research the issue of inclusive education of children of preschool age.
Keywords: методологія; інклюзія; інклюзивна освіта; інтеграція; інтегрована освіта